Attachment, Self-Esteem and Shame in Emerging Adulthood. (2nd June 2015) - Passanisi, Alessia; Gervasi, Alessia Maria; Madonia, Carmela; Guzzo, Giovanni; Greco, Davide
Abstract: Attachment styles are critical to the organization and representation of self and for regulating emotions. 209students between the ages of 19 and 24 completed three self-report measures on attachment styles, self-esteem and feelings of shame. Males showed higher self-esteem and lower feelings of shame. In the entire sample, securely attached students reported a higher level of self-esteem and a lower level of shame than insecurely attached students. Moreover, this study showed a relationship between insecure attachment, low self-esteem and shame.The present study suggests the relevance of attachment styles and self-esteem for the understanding of feelings of shame among emerging adults.This can have important implications for the development of preventative measures to reduce the risk of a disorder.